Comparison of Surgical and Cadaveric Intestine as a Source of Crypt Culture in Humans. (8th September 2020) - Scott, Andrew; Olack, Barbara; Rouch, Joshua D.; Khalil, Hassan A.; Kokubun, Brent A.; Lei, Nan Ye; Wang, Jiafang; Solorzano, Sergio; Lewis, Michael; Dunn, James C.Y.; Stelzner, Matthias G.; Niland, Joyce C.; et al.
Human small intestinal crypts are the source of intestinal stem cells (ISCs) that are capable of undergoing self-renewal and differentiation to an epithelial layer. The development of methods to expand the ISCs has provided opportunities to model human intestinal epithelial disorders. Human crypt samples are usually obtained from either endoscopic or discarded surgical samples, and are thereby exposed to warm ischemia, which may impair their in vitro growth as three-dimensional culture as spheroids or enteroids. In this study we compared duodenal samples obtained from discarded surgical samples to those isolated from whole-body preserved cadaveric donors to generate in vitro cultures. We also examined the effect of storage solution (phosphate-buffered saline or University of Wisconsin [UW] solution) as well as multiple storage times on crypt isolation and growth in culture. We found that intestinal crypts were successfully isolated from cadaveric tissue stored for up to 144 h post-procurement and also were able to generate enteroids and spheroids in certain media conditions. Surgical samples stored in UW after procurement were sufficiently viable up to 24 h and also allowed the generation of enteroids and spheroids. We conclude that surgical samples stored for up to 24 h post-procurement in UW solution allowed for delayed crypt isolation and viable in vitro cultures. Furthermore, in situ, hypothermic preservation in cadaveric duodenal samples permitted crypt/ISC isolation, and successful culture of spheroids and enteroids from tissues held for up to 6 days post-procurement.